Preventive Administration of Non-Allergenic Bet v 1 Peptides Reduces Allergic Sensitization to Major Birch Pollen Allergen, Bet v 1 - Akinfenwa, Oluwatoyin; Huang, Huey-Jy; Linhart, Birgit; Focke-Tejkl, Margarete; Vrtala, Susanne; Poroshina, Alina; Nikonova, Alexandra; Khaitov, Musa; Campion, Nicholas J.; Eckl-Dorna, Julia; Niederberger-Leppin, Verena; Kratzer, Bernhard; et al. (Frontiers in Immunology, 2021)
IgE-mediated allergy to birch pollen affects more than 100 million patients world-wide. Bet v 1, a 17 kDa protein is the major allergen in birch pollen responsible for allergic rhinoconjunctivitis and asthma in birch pollen allergic patients. Allergen-specific immunotherapy (AIT) based on therapeutic administration of Bet v 1-containing vaccines is an effective treatment for birch pollen allergy but no allergen-specific forms of prevention are available. We developed a mouse model for IgE sensitization to Bet v 1 based on subcutaneous injection of aluminum-hydroxide adsorbed recombinant Bet v 1 and performed a detailed characterization of the specificities of the IgE, IgG and CD4+ T cell responses in sensitized mice using seven synthetic peptides of 31-42 amino acids length which comprised the Bet v 1 sequence and the epitopes recognized by human CD4+ T cells. We then demonstrate that preventive systemic administration of a mix of synthetic non-allergenic Bet v 1 peptides to 3-4 week old mice significantly reduced allergic immune responses, including IgE, IgG, IgE-mediated basophil activation and CD4+ T cell responses to the complete Bet v 1 allergen but not to the unrelated major grass pollen allergen Phl p 5, without inducing Bet v 1-specific allergic sensitization or adaptive immunity. Our results thus demonstrate that early preventive administration of non-allergenic synthetic T cell epitope-containing allergen peptides could be a safe strategy for the prevention of allergen-specific IgE sensitization.